Day 1 Mon, October 26, 2020 2020
DOI: 10.2118/202065-ms
|View full text |Cite
|
Sign up to set email alerts
|

Results of Implementing An Integrated Approach to Modeling, Planning and Conducting of Hydraulic Fracturing on Bazhenov Shale

Abstract: During the Bazhenov shale development, a new integrated approach to planning the multistage hydraulic fracturing was developed. This approach is applied to each drilled well,thus implementing the strategy of technological experiment, where the well serves as a separate testing ground for testing the developed methods and implementing new technologies.With the help of modern multistage hydraulic fracturing modeling tools, developed jointly with technological partners for the project tasks, a technological exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The study showed that the adsorption is higher in reservoirs with lower permeability due to nanopore confinement effects. Korobitsyn et al [123] presented an integrated approach of modeling, planning, and conducting a multistage hydraulic fracturing operation. The study introduced the injection of fluids of different viscosity at different stages of the hydraulic fracturing process.…”
Section: Core Reservoir Scale: Hydrodynamic Modelingmentioning
confidence: 99%
“…The study showed that the adsorption is higher in reservoirs with lower permeability due to nanopore confinement effects. Korobitsyn et al [123] presented an integrated approach of modeling, planning, and conducting a multistage hydraulic fracturing operation. The study introduced the injection of fluids of different viscosity at different stages of the hydraulic fracturing process.…”
Section: Core Reservoir Scale: Hydrodynamic Modelingmentioning
confidence: 99%